Automated library booktruck for traditional libraries - JJ Spies; B Kotze (Institute of Advanced Engineering and Science, 2019)
Libraries are an integral part of our society’s knowledge repository and even though technological advances such as the internet, smart devices and an ‘always-connected-society’, provide avenues for fast and almost instantaneous access to knowledge, libraries still provide a physical place for the collection and dissemination of knowledge. The prompt shelving of the physical returned library books is an important task in any traditional library. To help speed up the shelving process, this paper proposed and simulated an automated booktruck that is capable of moving returned library books from the return desk back to the shelves. The simulation models currently available robotic hardware and implemented path finding and localization. The simulation results showed that returned books can be delivered to the shelves four times faster than the by using the current practices.